First assessment for the presence of phlebotomine vectors in Bavaria, Southern Germany, by combined distribution modeling and field surveys. - Simone Haeberlein; Dominik Fischer; Stephanie Margarete Thomas; Ulrike Schleicher; Carl Beierkuhnlein; Christian Bogdan (PLoS ONE, 2013)
Leishmaniasis is caused by protozoa of the genus Leishmania and transmitted by sand flies from mammalian reservoirs to humans. In recent years, a northward spread of L. infantum from highly endemic Mediterranean countries into previously non-endemic Central European areas has been suspected based on presumed sporadic cases of autochthonous leishmaniasis. Here, we investigated whether sand flies are prevalent in Bavaria in Southern Germany, a federal state in which autochthonous cases have previously been reported. Considering the present and future climatic conditions, we determined whether Bavaria is suitable for five sand fly species with assumed spreading tendencies towards Central Europe: Phlebotomus ariasi, P. neglectus, P. perfiliewi and P. perniciosus that are known vectors for Leishmania in Europe, and P. mascittii, a suspected but not proven vector. Within Bavaria we defined sampling regions based on their climatic suitability and their spatial distance to the sites of the autochthonous cases and/or to areas of reported sand fly detection in states adjacent to Bavaria. At 155 locations in 7 sampling regions, CDC light traps were placed during 38 nights in the summers of 2009 and 2010, resulting in 202 trap-nights. All traps were negative for sand flies. The results suggest that Bavaria is not yet endemic for sand flies, but do not exclude the possibility of sporadic cases of autochthonous human or zoonotic Leishmania infections. This study, which combined methodological approaches from different disciplines, serves as reference for future surveys and risk analyses of sand flies and leishmaniasis in so far non-endemic areas of Europe.